Study on effect of compound surfactants on wettability of bituminous coal and its microscopic mechanism - Changbo DU; Chuanwang CHENG; Fu YI; Huijie HUANG; Weize SUN; Han TAO (Meitan kexue jishu)
Coal dust pollution is an urgent engineering problem that needs to be solved, and traditional spray technology has made it difficult to meet modern industrialization requirements. To solve the problem of coal dust pollution, based on spray technology used to improve the wetting performance of water spray additives on coal dust, four surfactants, namely, Fast Penetrant T (Fast T), Decyl Glucoside (APG), Trillatone 100 (TX−100) and Cocoamidopropyldimethylamine Oxide (CAO), were selected, and the single and composite wetting characteristics were investigated throughout the wetting time. XPS was used to analyze the changes in elemental content before and after the action; molecular dynamics were used to simulate the changes in water/coal, water/surfactant and composite surfactant before and after the action. XPS was used to analyze the changes in elemental composition before and after the action of the composite surfactants; molecular dynamics was used to simulate the interactions between water/coal and water/surfactant/coal and to analyze the relative concentrations, mean square displacements, and interaction energies between the surfactants and coal. The experimental results showed that the wetting time decreased with increasing surfactant concentration, and the wetting time of coal dust in the four surfactant solutions tended to stabilize above a mass concentration of 0.2%. The combination of TX−100 and CAO had an antagonistic effect on the wetting time of coal dust; the combination of Fast T and APG or TX−100 had a synergistic effect, and the synergistic effect was strongest when the mass ratio of Fast T to APG was 2∶2. Compared with those of the same concentration of Fast T and APG monomer solution, the wetting time was 54.82% and 50.54% lower, respectively; there were obvious C and O peaks in the XPS spectrum; additionally, the effect of the C—O functional group on the wettability of coal dust was the most significant. Similarly, the overlap area between the water peaks of the composite surfactant and the coal peaks was greater, and the surfactant promoted the adsorption of water molecules on the surface of the coal dust so that more water molecules moved toward the coal surface. Similarly, the water/coal surface of the compound had a larger overlap area, and the water/coal surface of the compound had a larger overlap area. On the coal surface, the interaction energies of water/coal, water/single surfactant, and water/complex surfactant are all negative, and the magnitude of their interaction energies follows the order water/complex surfactant coal < water/single surfactant/coal < water/coal system. The compounded surfactant has better wetting properties than the single surfactant, which is manifested by the shortening of the wetting time at the macroscopic level and the increase in the negative interaction energy between coal and water at the microscopic level. The results of the study can provide some reference for the selection and design of surfactants for coal dust wetting.